Factors Related to Contact Dermatitis in Metal Industrial Workers 2022 - Fajar Afifatur Rahmah; Robiana Modjo (Universitas Airlangga, 2022)
Introduction: The metal industry plays an essential role in rapid economic growth. The growth is straight with the worker increment and high occupational disease risk. Various materials, especially in the metal industry, can initiate contact dermatitis in the workplace. Skin is the organ that exposes frequently, and skin disease is the most common disease among occupational dermatitis. Allergens and irritants exposure contribute to contact dermatitis. In Indonesia, occupational skin diseases are 97%, and Irritant Contact Dermatitis (ICD) is the most case, around 66.3%. This study aims to describe the influencing factors of contact dermatitis in metal industries workers. Methods: The study is a literature review using the electronic database search, namely Google Scholar, Research Gate and Garuda. The keywords occupational contact dermatitis and metal contact dermatitis are applied. The inclusion criteria are online databases from 2017 to 2022, completed articles, relevant titles and abstracts. Exclusion criteria include not completed articles, not relevant titles and abstracts. Results: The twelve articles use the same method, namely cross-sectional design. The questionnaire, observation, and interview were applied for the data collection method. This literature review presents factors influencing contact dermatitis: work duration, contact duration, wearing personal protective equipment (PPE), and personal hygiene. The articles reviewed collection are obtained through descriptive tests and analytical. Conclusion: As the review result that there are affected factors to contact dermatitis: contact duration, frequency duration, PPE usage, and personal hygiene. PPE is the dominant influencing factor to metal contact dermatitis.